Modelagem dos fatores que afetam o comportamento ambiental de residentes em destinos turísticos costeiros - Soares, Amanda Mirely Cipriano (2017)
The Brazilian coastal zone is considered a relevant tourist destination, becoming one of the most important places for national and international tourists. However, there is a significant environmental impact generated by the activity, mainly in relation to water pollution, reef destruction, sand dune removal, undue construction, among others. In this sense, the aim of this study was to investigate the relations of dependence between factors affecting resident environmental behavior in coastal tourist destinations, aiming to contribute with the definition of better environmental management actions for coastal tourist destinations. For that, a descriptive, quali-quantitative study was proposed, using the hypothetical-deductive method, because of some theoretical models are used to arrive at the construction of hypotheses. The study had as object, the residents of Baía Formosa, site, located on the south coast of Rio Grande do Norte, 98.9 km from Natal, considering a sample of the non-probalistic type that resulted in the application of a total of 288 questionnaires. The data collection instrument contains dimensions and variables based on the Theory of Planned Behavior (Ajzen, 1985), specifically Behavioral Intent, Pro-Environmental Attitude, Subjective Norms and Perceived Behavioral Control, with the addition of Place Attachment construct to the model which, according to the literature, can influence the behavior investigated. The variables composing these dimensions were evaluated using a eleven-point scale (based on Likert Scale), which ranged from 0 (I strongly disagree) to 10 (I fully agree), according to the level of agreement with the proposed sentence to characterize each variable. Data collected were analyzed by descriptive statistics method and Structural Equations Modeling. Findings show that variables of rational character have a greater explanatory power of the residents environmental behavior than variables of affective character.